2013
DOI: 10.1007/s10620-013-2608-y
|View full text |Cite
|
Sign up to set email alerts
|

ERCP with Probe-Based Confocal Laser Endomicroscopy for the Evaluation of Dominant Biliary Stenoses in Primary Sclerosing Cholangitis Patients

Abstract: pCLE achieves a high technical success rate in patients with PSC and DS. This single center, small series, suggests that pCLE may have a high sensitivity and negative predictive value to exclude neoplasia. If verified in larger prospective studies, the technology may be utilized to risk stratify dominant strictures in patients with PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…A total of 21 studies met inclusion criteria: 13 studies on bile duct brushing ( n = 809), 4 studies evaluating FISH trisomy ( n = 629), 7 studies evaluating FISH polysomy ( n = 701), 2 studies on probe‐based confocal laser endomicroscopy ( n = 66), and 4 studies on single‐operator cholangioscopy with targeted biopsies ( n = 128) . Characteristics of the included studies are demonstrated in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies met inclusion criteria: 13 studies on bile duct brushing ( n = 809), 4 studies evaluating FISH trisomy ( n = 629), 7 studies evaluating FISH polysomy ( n = 701), 2 studies on probe‐based confocal laser endomicroscopy ( n = 66), and 4 studies on single‐operator cholangioscopy with targeted biopsies ( n = 128) . Characteristics of the included studies are demonstrated in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although SOC seems to be useful in the assessment of suspicious strictures in patients with sclerosing cholangitis, the diagnostic workup of these patients remains challenging. Recently, cholangioscopy with narrow-band imaging [20] or probe-based confocal laser endomicroscopy [21] has reported to be promising diagnostic modalities in patients with PSC. Further prospective studies are warranted in order to define the role of SOC in the assessment of strictures in sclerosing cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although cholangioscopically directed biopsy of the bile duct seems ideal, no major studies have demonstrated a greater diagnostic yield in the evaluation of CCA. Probe‐based confocal endomicroscopy, a new diagnostic tool that allows subepithelial evaluation of biliary mucosa, has also been studied in small numbers of patients with PSC alone or with CCA . Similar to cholangioscopy, probe‐based confocal endomicroscopy appears promising, but only two currently available studies have described this modality in this patient population.…”
Section: Endoscopic Diagnosismentioning
confidence: 99%